Assesment of safety awareness among KWSP Headquaters employees - Mohd Salleh, Rizal (2001)
This project is aimed at producing a general overview of the KWSP Head quarters on safety awareness and subsequently recommends improvement for better awareness. The employees were given the questionnaires with regards on the safety and health issues; policy and arrangement, training, knowledge and attitude and environment. The data was subsequently analysed by using computer statistical software and followed with discussions. The assessment conducted showed that there is a reasonably acceptable safety awareness among the employees. Anyhow, the role and commitment from the Safety and Health committee and training on first aid are the main elements identified to contribute to low score percentage on overall result.